Pengaruh Pancasila Terhadap Kehidupan Beragama dan Nasionalisme di Lingkungan Kampus Politeknik Negeri Ketapang Program Studi Teknologi Hasil Perkebunan - Isye Selvianti; Marisa Nopriyanti; Khairul Muttaqin (JUSTITIA JURNAL HUKUM, 2026)
This study aims to examine, from both juridical and sociological perspectives, the implementation of Pancasila values in religious life within higher education institutions, as well as to analyze the role of Pancasila as a fundamental legal norm in fostering interreligious tolerance and strengthening nationalism among university students. As the state ideology, the source of all sources of law, and the philosophical foundation of the Indonesian legal system, Pancasila occupies a strategic position in shaping national character, particularly within the context of social interaction and religious life in higher education. This research employs a normative–empirical legal research method using statutory, conceptual, and sociological approaches. The research subjects consist of students from the Agro-Industrial Technology Study Program at the Ketapang State Polytechnic, with samples drawn from second-, fourth-, and sixth-semester students. The data are analyzed to assess the relationship between the normative legal framework of Pancasila and its practical implementation in campus religious life. The findings indicate that religious diversity within the higher education environment does not result in significant conflict, as Pancasila values have been substantively internalized in students’ attitudes and behavior. Pancasila functions not merely as an ideological principle but also as an effective normative legal guideline in cultivating a culture of tolerance and reinforcing students’ sense of national identity and nationalism. These findings are consistent with the constitutional mandate, particularly Article 31 of the 1945 Constitution of the Republic of Indonesia, as well as the objectives of national education as regulated under the prevailing laws and regulations.